Wortmannin-induced vacuole fusion enhances amyloplast dynamics in Arabidopsis zigzag1 hypocotyls - Alvarez, Ashley Ann (Journal of experimental botany, 2016)
© The Author 2016. Published by Oxford University Press on behalf of the Society for Experimental Biology.